2019
DOI: 10.7759/cureus.4785
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Artery Dissection and Takotsubo Syndrome Associated with Marijuana Use

Abstract: Cervical artery dissection is an intimal tear in a cervical artery with the development of intramural hematoma resulting in stenosis, occlusion, or aneurysmal dilation. Takotsubo syndrome (TTS) is characterized by acute heart failure with a distinctive regional left ventricular contraction profile. We presented the case of a 33-year-old male who visited the emergency department due to right-sided arm/leg weakness, slurred speech and transient loss of right eye vision. The patient was diagnosed with vertebral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
(19 reference statements)
3
2
0
Order By: Relevance
“…Research by Seba et al and Ghosh et al [13,14] indicated that congenital malformations are commonly observed in mothers over the age of 30, while our study showed that most mothers of neonates with congenital anomalies were between 18 and 30 years of age. Our results are consistent with the study by Sanchez-Nadales et al, which showed that most mothers of neonates with congenital anomalies were between 20 and 35 years of age [12]. Similar findings were reported by Tiwari and Gupta [15].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Research by Seba et al and Ghosh et al [13,14] indicated that congenital malformations are commonly observed in mothers over the age of 30, while our study showed that most mothers of neonates with congenital anomalies were between 18 and 30 years of age. Our results are consistent with the study by Sanchez-Nadales et al, which showed that most mothers of neonates with congenital anomalies were between 20 and 35 years of age [12]. Similar findings were reported by Tiwari and Gupta [15].…”
Section: Discussionsupporting
confidence: 94%
“…The high prevalence of congenital malformations in males could be because the female babies were affected by more lethal congenital malformations; so, they could not survive being born with signs of life [ 22 ]. In our present study, a higher birth weight was associated with a higher rate of congenital malformations, which is consistent with the findings from Sanchez-Nadales et al [ 12 ] and Singh et al [ 9 ]. However, this contradicts the findings of Seba et al [ 13 ] who reported a high rate of congenital malformations in fetuses with lower birth weights.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations